Morphology control and temperature sensing properties of micro‐rods NaLa(WO4)2:Yb3+, Er3+ phosphors. Issue 1 (1st September 2020) - Xiao, Qi; Dong, Xinyao; Yin, Xiumei; Wang, Hong; Yu, Weiguang; Zhong, Hua; Xing, Mingming; Tian, Ying; Fu, Yao; Dong, Bin; Luo, Xixian
Abstract: Uniform spindle‐like micro‐rods NaLa(WO4 )2 :Yb 3+, Er 3+ phosphors are prepared by the solvothermal method in the text. Controllable morphology of NaLa(WO4 )2 crystal can be obtained by adjusting the prepared temperature, PH value, complexing agent content, and solvent ratio. Uniform NaLa(WO4 )2 :Yb 3+, Er 3+ micro‐rods of 1.8 μm in length and 0.5 μm in width are synthesized at a low temperature of 120°C. The prepared NaLa(WO4 )2 :Yb 3+, Er 3+ phosphors present green upconversion luminescence under 980 nm excitation, luminescence intensity reaches to maximum at the Yb 3+ and Er 3+ concentration of 6 and 2 mol%. The temperature performance of the NaLa(WO4 )2 :Yb 3+, Er 3+ phosphors are evaluated based on thermal coupling technology. Temperature dependence of the two green emissions ratio of Er 3+ ion is obtained, and the sensitivity of the sample can be calculated, the maximum sensitivity of NaLa(WO4 )2 :Yb 3+, Er 3+ is up to 0.019 K −1 at the sample temperature of 564 K.